Agama Sipil di Amerika Serikat: Telaah Terhadap Gagasan dan Peran Robert N. Bellah - Ahmad Sahidah (Universitas Trunojoyo Madura, 2019)
This article will unravel the emergence of civil religion in the United States that cannot be separated from America’s long history, since the civil war, the declaration of independence and the influence of enlightenment and Christian values (especially Protestantism) that are deeply embedded in the American people. He was born as a recognition of the highest values, not one of the denominations of Christianity itself. At the same time, as a criticism of the use of religious symbols in official state practice. With the hermeneutic reading of Bellah’s works, it can be concluded that civil religion is inevitable, because each group has a religious dimension. To say that there is no civil religion, is to say that the civitas, the civil order itself does not exist, it should not appear. Each group produces communal symbols and rituals that give instructions and tie them together. Thus, civil religion does not only belong to America, it can belong to other nations in the world.